The buried medieval pasture of Onoldswil (Niederdorf BL, Switzerland, ad 1295): an example of a well preserved palaeobiocoenosis - Akeret, Örni; Kiefer, Simone; Kühn, Marlu; Rentzel, Philippe; Rösch, Manfred; Wick, Lucia (Vegetation history and archaeobotany, 2018)
In the late spring of the year ad 1295 a landslide devastated the village of Onoldswil in the Swiss Jura mountains. During recent construction work, a small area of the original land surface was unearthed. The 5 m of compacted clay deposited by the landslide had caused the complete exclusion of oxygen and underneath it the excavators came upon mosses, blades of grasses and other plants that were still green. Below the vegetation cover the humus horizon with subterranean plant parts appeared. Samples were taken for plant macro- and microfossil and geoarchaeological analyses. This offered the rare opportunity to study the vegetation and the topsoil of a small area of land preserved in situ as an autochthonous palaeobiocoenosis, the preserved original combination of the plant community which grew there. Grassland taxa dominated the pollen and macrofossil spectra. Compacted zones within the humus horizon, the plant taxa composition and the presence of spores of coprophilous fungi showed that this place had once been a nutrient-rich pasture. Grazing animals had favoured the spread of juniper. Manuring seems to have taken place. The slopes of the surrounding mountains had been largely cleared of woodland, which may have been the cause of the landslide. The disaster probably happened in late spring, because entire fruiting capitula of Taraxacum officinale (dandelion) were found. Landslides are catastrophic events, destroying the soils and everything that lives in and on them on their way downhill. In places, however, they can also blanket the original land surface and its vegetation and create an archive of ancient life.